PENINGKATAN PRESTASI KERJA MELALUI PELATIHAN DAN KEDISIPLINAN KERJA - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
The objective of this research was to analyze the effect of the training and discipline on the employee performance in De Green City hotel Bandar Lampung. Type of this research wa quantitative research using an associative method. Population of this research was De Green City hotel employees. The number of this sample was 39 respondents. Data collecting technique used in this research was questionnaires. Data Analysis technique used in this research was a multiple linier regression. Moreover, the hypothesis test was t-test and F-test. The result of this research showed that (1) the training affected the employee performance; (2) the discipline affected the employee performance; and, (3) the training and discipline simultaneously affected the employee performance.